2016
DOI: 10.1007/s10854-016-5224-8
|View full text |Cite
|
Sign up to set email alerts
|

Roll-to-roll processed PEDOT:PSS thin films: application in flexible electrochromic devices

Abstract: In this paper, poly (3,4-ethylenedioxythiophene) doped with poly(styrene sulfonic acid) denoted as PED-OT:PSS, a common material used as electrode in organic electronics or as charge balancing layer in electrochromic devices, was processed in thin film by roll-to-roll technique onto flexible substrate. Improved wettability was achieved when the ITO/PET substrate received a pre-treatment with isopropyl alcohol (iPrOH) and small amount of this alcohol was mixed with the PEDOT:PSS, as demonstrated by the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…PEDOT:PSS films have also found use as transparent electrodes for electrochromic polymers and other applications . While electrochromic polymers on these films switch more rapidly than on doped PE 2 , the films are significantly more colored than the PE 2 ‐based films due to tailing of the PEDOT bipolaron band . This difference between the color neutrality of oxidized PE 2 and PEDOT has been previously investigated and can be quantitatively observed by comparing the colorimetry of doped PE 2 films, either with (Figure b) or without (Figure S4b, Supporting Information) an oxidized film of PProDOT, with the reported values for PEDOT:PSS .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…PEDOT:PSS films have also found use as transparent electrodes for electrochromic polymers and other applications . While electrochromic polymers on these films switch more rapidly than on doped PE 2 , the films are significantly more colored than the PE 2 ‐based films due to tailing of the PEDOT bipolaron band . This difference between the color neutrality of oxidized PE 2 and PEDOT has been previously investigated and can be quantitatively observed by comparing the colorimetry of doped PE 2 films, either with (Figure b) or without (Figure S4b, Supporting Information) an oxidized film of PProDOT, with the reported values for PEDOT:PSS .…”
Section: Resultsmentioning
confidence: 82%
“…Energy Mater. [19,23,43,46,47] This difference between the color neutrality of oxidized PE 2 and PEDOT has been previously investigated [19] and can be quantitatively observed by comparing the colorimetry of doped PE 2 films, either with ( Figure 3b) or without ( Figure S4b, Supporting Information) an oxidized film of PProDOT, with the reported values for PEDOT:PSS. This switching is reversible, albeit somewhat slower compared to using an ITO electrode due to the lower conductivity of doped PE 2 ( Figure S7, Supporting Information).…”
Section: Evaluation Of Pe 2 As a Transparent Electrode Materialsmentioning
confidence: 68%
“…This is in good agreement with the current switching behavior of archetypical organic-based ECD devices. 34 36 …”
Section: Resultsmentioning
confidence: 99%
“…PEDOT:PSS-based electrochromic displays can operate through electronically-induced ion transfer from electrolytes to the PEDOT:PSS electrodes. [30][31][32] Therefore, it was suggested that the…”
Section: Electrochromic Paper Devicementioning
confidence: 99%